Identification of PDGF-BB binding to thymosin ?4 by chemical cross-linking - Knop, Jana; App, Christine; Huff, Thomas; Iavarone, Federica; Castagnola, Massimo; Hannappel, Ewald (Expert Opinion on Biological Therapy, 2015)
The purpose of our work was to identify unknown interaction partners of thymosin ?4 (T?4). It was suggested that T?4 could be an antifibrotic drug for treatment of liver fibrogenesis, because T?4 prevents the platelet-derived growth factor-BB (PDGF-BB)-induced activation of hepatic stellate cells (HSCs). Very little information is available how T?4 counteracts the PDGF-BB-induced activation of HSCs. We propose the hypothesis that T?4 could bind directly to PDGF-BB and thereby reduce the concentration of free PDGF-BB available for binding to the PDGF-? receptor.To prove our suggestion of a direct interaction between T?4 and PDGF-BB, we carried out chemical as well as photochemical cross-linking experiments between the two pure proteins in vitro.We identified an interaction between T?4 and PDGF-BB by 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide (EDC) cross-linking as well as through biotin label transfer using a bifunctional photoactivatable derivative of T?4. In an in vitro system, PDGF-BB was identified as the first extracellular partner interacting with T?4. This interaction could influence PDGF-BB binding to its receptor and abolish PDGF-BB-related effects.Direct interaction of T?4 with extracellular factors should be considered as a potential mechanism to explain the pleiotropic effects of ?-thymosins.
EVALuna2:4957